A novel Pinellia ternata catalase gene PtCAT2 regulates drought tolerance in Arabidopsis by modulating ROS balance - Xu, Juanjuan; Du, Ni; Dong, Tianci; Zhang, Han; Xue, Tao; Zhao, Fei; Zhao, Fenglan; Duan, Yongbo; Xue, Jianping (Frontiers in Plant Science, 2023)
Drought is one of the major abiotic stresses limiting agricultural production, particularly for shallow-rooted plants like Pinellia ternata. It damages plants via oxidative burst, but this effect could be mitigated by catalase (CAT). However, no studies have been reported on CAT homologs in P. ternata, a drought-sensitive plant species. In the present study, a novel CAT gene, PtCAT2, was functionally characterized via overexpression in Arabidopsis and analysis of cis-elements in its promoter. The isolated CAT gene was 1479 bp and encoded a protein containing 242 amino acids. The protein contains the CAT activity motif and the heme-binding site of a typical CAT, and the subcellular analysis indicated that the protein localizes at the cytoplasm and membrane. Moreover, the quantitative real-time reverse transcription PCR indicated that PtCAT2 is expressed ubiquitously in P. ternata and is strongly induced by drought stress and abscisic acid (ABA) signals. PtCAT2 overexpression enhanced the drought tolerance of Arabidopsis, as shown by the 30% increase in plant survival and a five-fold- increase in CAT activity. Moreover, PtCAT2-transgenic plants increased superoxide dismutase and peroxidase activities and reduced malondialdehyde, membrane leakage, and hydrogen peroxide (H2O2) (P<0.05). Furthermore, PtCAT2-transgenic plants showed higher tolerance to oxidative stress caused by exogenous H2O2 and retained higher chlorophyll and water contents than the WT. The mitochondria function was better maintained as presented by the higher oxygen consumption rate in transgenics under drought stress (P<0.05). The endogenous CATs and drought response-related genes were also upregulated in transgenic lines under drought stress, indicating that PtCAT2 confers drought stress tolerance by enhancing the H2O2 scavenging ability of plants to maintain their membrane integrity. These results improve our understanding of the drought response mechanisms and provide a potential breeding strategy for P. ternata genetic improvement.